The Impact of Implementation of TQM Practices on Innovation in the Palestinian Service Companies - Herzallah, Ahmad; Shoqeir, Ne’meh (Jordan Journal of Business Administration, 2021)
The purpose of this study was to examine the impact of implementation of TQM practices on innovation in the Palestinian service companies. Descriptive analytical approach was utilized in this study, by designing a questionnaire consisting of (65) paragraphs distributed over (13) dimensions divided into two parts. The first part includes eight TQM practices, while the second part includes five dimensions of innovation. The questionnaire was distributed to all members of the population of the study in Palestinian service companies. A purposive sample of 220 employees of the service companies was taken in the study, which includes (general managers, executive directors, deputy general managers, as well as quality, management and productivity directors). The scale had a high degree of reliability and validity. Results derived from this study show that TQM practices (soft TQM practices and hard TQM practices) have a positive and significant impact on all kinds of innovation (incremental product innovation, incremental process innovation, radical product innovation, radical process innovation and administrative innovation).